Association of gestational diabetes and breastfeeding on obesity prevalence in predominately Hispanic low‐income youth. Issue 3 (7th July 2014) - Shearrer, G. E.; Whaley, S. E.; Miller, S. J.; House, B. T.; Held, T.; Davis, J. N.
Summary Objective The goal of this study was to examine if breastfeeding duration by gestational diabetes mellitus status impacted the prevalence of obesity in offspring. Methods Data were obtained from a 2011 phone survey with caregivers of low‐income children (2–4 years) participating in the Women, Infants and Children programme in Los Angeles County. The final sample included 2295 children, 84% Hispanic and 48% female. Chi‐square and binary logistic regression were used to assess gestational diabetes status and breastfeeding duration on the prevalence of obesity, with the following a priori covariates: child's ethnicity, birth weight, age in months and sex. Results Breastfeeding and gestational diabetes were significantly associated with obesity prevalence (P < 0.01). Using gestational diabetes mellitus and no breastfeeding as the referent category, gestational diabetes mellitus offspring who were breastfed ≥12 months had a 72% decrease in obesity prevalence (adjusted odds ratio = 0.28, confidence interval 0.89–0.03, P = 0.05). Conclusions These findings suggest that > 12 months of breastfeeding duration in the gestational diabetes mellitus group and any duration of breastfeeding in the non‐gestational diabetes mellitus mothers is needed to reduce obesity levels in a primarily Hispanic population.